(untitled) (Indian Journal of Nematology, 2024)
Three tomato cultivars viz., Arka Samrat, Saaho and SVTD8323 grafted on Meloidogyne incognita-resistant Solanum torvum, were evaluated for plant growth parameters and nematode damage. The results revealed that tomato cultivars grafted on S. torvum had a significantly lower number of galls (9–10 per root system), egg masses (8–9 per root system) and number of eggs per egg mass (77–82), compared to non-grafted plants (72–76 galls per root system, 41–42 egg masses per root system, and 229–236 eggs per eggmass). In grafted cultivars under nematode-infested conditions, significantly longer shoot (58.5 to 61.4 cm) and root length (11.7 to 12.9 cm), fresh weight of shoot (25.80 to 26.49 g) and root (4.59 to 4.87 g) were observed than in the corresponding non-grafted cultivars. This study revealed that S. torvum as a rootstock exhibited the resistance response to M. incognita and also averted a reduction in growth parameters in tomato cultivars due to M. incognita, indicating its usefulness as rootstock for management of root-knot nematodes in tomato crop